2020
DOI: 10.1186/s12911-020-01329-1
|View full text |Cite
|
Sign up to set email alerts
|

Development of a support vector machine learning and smart phone Internet of Things-based architecture for real-time sleep apnea diagnosis

Abstract: Background The breathing disorder obstructive sleep apnea syndrome (OSAS) only occurs while asleep. While polysomnography (PSG) represents the premiere standard for diagnosing OSAS, it is quite costly, complicated to use, and carries a significant delay between testing and diagnosis. Methods This work describes a novel architecture and algorithm designed to efficiently diagnose OSAS via the use of smart phones. In our algorithm, features are extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…Future efforts to provide resources on TBDs for healthcare providers should take into consideration where and how this information will be accessed. In addition, resources developed with shared decision-making and clinical decision support incorporated have demonstrated positive effects on patient-provider communication in other areas of healthcare [ 6 , 20 23 ]. Similar resource development targeting TBDs may prove beneficial for challenging scenarios described by clinicians in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Future efforts to provide resources on TBDs for healthcare providers should take into consideration where and how this information will be accessed. In addition, resources developed with shared decision-making and clinical decision support incorporated have demonstrated positive effects on patient-provider communication in other areas of healthcare [ 6 , 20 23 ]. Similar resource development targeting TBDs may prove beneficial for challenging scenarios described by clinicians in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The types of digital biomarkers used in these studies varied according to the disorder. In most studies, measurements such as ECG, 34 37 pulse rate, 39 and acceleration 32 35 36 were collected as digital biomarkers since the subjects’ body data or location data were required in their daily lives. In particular, watches 34 36 and waist- or writstbands 32 were widely used, as were voice recognition, 37 smartphones, 38 40 41 and portable sensors.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, watches 34 36 and waist- or writstbands 32 were widely used, as were voice recognition, 37 smartphones, 38 40 41 and portable sensors. 39 The biomarker collection methods varied according to the type of biomarker and type of disability. Derungs, et al 35 used wearable motion sensors as they could monitor patient movements in daily life without specific tests, which can be burdensome for patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Internet of Things (IOT) architecture enables real-time monitoring of human physiological parameters, combined with diagnostic algorithms to provide early warnings of abnormal data ( 47 ). Studies led by Ma et al suggested that deep learning methods achieve robust sleep staging results of both portable and in-hospital EEG recordings.…”
Section: Alternative Sleep Monitoring In Nementioning
confidence: 99%